A constitutive model optimizing superalloy performance: The interplay of annealing twins, dislocations, and grain boundaries - Zongpeng Tian; Rui Zhao; Xinshun Diao; Shan Jiang; Debin Shan; Min Wan (Journal of Materials Research and Technology, 2025)
The room temperature mechanical properties and formability of heat-treated ultrathin nickel-based superalloys are significantly influenced by annealing twins, dislocations, and grain boundaries. To elucidate the mechanistic roles of these microstructural features, this study employed high-precision planar argon ion polishing and electron backscatter diffraction to quantitatively characterize the annealing twin volume fraction, dislocation density, and grain size in superalloys heat-treated at various temperatures. A strengthening constitutive model coupling annealing twin volume fraction, dislocation density, and grain size was developed to quantify their individual contributions to the tensile flow stress, while systematically analyzing the complex interactions among annealing twins, dislocations, and grain boundaries. Results indicate that although dislocation multiplication is the dominant factor controlling peak flow stress, the evolution of annealing twins and grain boundaries after high-temperature treatment increasingly affects alloy strain hardening. Specifically, fine-grained structures are the primary factor for dislocation density multiplication, while high-density annealing twins further promote dislocation multiplication, thereby amplifying dislocation strengthening. Moreover, the contribution of annealing twin spacing to alloy strength is notably higher than that of annealing twin volume fraction. During deformation, fine grains accelerate annealing twin decomposition, while higher dislocation density reduces residual annealing twin components, jointly diminishing annealing twin strengthening. Concurrently, high dislocation density promotes grain refinement and enhances grain boundary strengthening, whereas abundant annealing twin volume fraction weakens this effect. This study deepens the understanding of how annealing twins, dislocations, and grain boundaries influence the deformation mechanisms of superalloys, providing a theoretical foundation for optimizing heat treatment processes to achieve desired mechanical properties.